Pengaruh Kompetensi Sumber Daya Manusia dan Sistem Pengendalian Internal Terhadap Akuntabilitas Pengelolaan Dana Desa di Kabupaten Enrekang - Andi Nurhaeda; Baiq Solatiyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Adequate human resource competency supported by an internal control system is expected to create accountable and transparent village fund management. This study was conducted to determine the effect of human resource competency and internal control system on the accountability of village fund management in Enrekang district. This study uses primary data obtained from respondents' answers to the distributed questionnaires. The sampling technique used was purposive sampling so that 56 respondents were obtained. The data was processed using SPSS and analyzed using multiple regression analysis. The results of the study indicate that partially human resource competency and internal control system have a positive and significant effect on the accountability of village fund management in Enrekang district.